Critical temperatures for the thermal explosion of chemicals (Industrial safety series, 2005)
The value of the critical temperature (Tc), below which the thermal explosion of a chemical cannot occur, is indispensable to prevent such a chemical from exploding. In order to determine the Tc it has so far been necessary to measure the value in explosion experiments. Because of the inherent hazards, only few Tc values are available at present. Critical Temperatures for the Thermal Explosion of Chemicals introduces new and simple procedures to calculate the Tc. As a result Tc can be calculated for a range of chemicals, many of which are listed in this new volume. The calculated values of Tc are shown to be in agreement with experimentally determined values. The data and methods presented in Critical Temperatures for the Thermal Explosion of Chemicals will be of use to research laboratories as well as in the chemical industry. * Introduces new and simple procedures for calculating critical temperatures * Lists the T(c) values of chemicals in tables * Explains mathematical expressions in clear simple terms.